PERSPEKTIF KESETARAAN GENDER DALAM BUKU BAHASA ARAB SISWA MTS PENDEKATAN SAINTIFIK 2013 - Shodiq, Muhammad Jafar (FENOMENA, 2016)
The curriculum evaluation is a necessity. In Indonesia, the latest implemented curriculum for schools and madrasah is 2013 scientific based-approach curriculum which has not been implemented in all levels of school yet. As a guidance of the implementation of 2013 curriculum for madrasah, the religious affairs minister has established a Guidance Book for students and teachers. The Indonesian government will gradually provide the Guidance Book for students and teachers covering all subject taught in the school, Arabic in particular. Recently, Indonesian government has established Arabic textbook for class X of Madrasah Aliyah, for class VII of Madrasah Tsanawiyah, and for class I and IV of Madrasaha Ibtidaiyah. This textbook is important in emerging the ideology for students. That is why, the development of discourse through the use of pictures and sentences become important since they are integrative and meaningful for students in organizing the information and concepts of a book. This paper describes the significance of the textbook in socializing and internalizing the moral characters as well as gender equality.